Decoding Cultural-Code Meaning of Allusion in Translations (Xi Jinping’s Speech at Davos Forum 2021) - T. N. Zubakina (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The results of the analysis of the rhetoric of Xi Jinping’s public speech are presented. The novelty of the research lies in an attempt of a comparative interpretation of allusive linguistic representations of the text of the speech and its translations into English and Russian. It is emphasized that the interpretation of linguistic representations or their decoding is possible in the contexts of linguacultural accents of allusions of the text and dictionary entries, since by its sign essence language is one of the codes of culture. The authors proceed from the fact that the allusion, being a cognitive category, has a cultural-code meaning (CC-meaning), which is reflected not only in the vocabulary conceptual content, but also in the system of extralinguistic knowledge, associations and images that acquire meaning, enshrined in the culture of linguistic community. The results of an interpretative analysis in order to identify allusive hidden meanings and cultural-code meanings of the units under study are presented in the article. An algorithm is proposed for the interpretative analysis of figurative units in the speech of Xi Jinping by comparing their representations in three languages. The question is raised that the allusions in the speech of the Chinese leader and their semantic correspondences in the translation texts are addressed both to the internal addressees / speakers of the Chinese language and to the external — foreign-language audience.